From the history of domestic aircraft engineering: little-known figures - Kryvokon, O. G. (History of science and technology, 2018)
The article is devoted to the highlighting of some little-known data about people who made a significant contribution to the formation and development of national aircraft engineering. Some facts of biographies are published for the first time, the main pieces of works in the creation and production of aircraft by engineers and designers as A.O. Batumov, O. Y. Belolipetskyi, O. V. Bolbot, V.A. Domenikovskyi, M.S. Trunchenkov are described.